Combinatorial optimization : 4th International Symposium, ISCO 2016, Vietri sul Mare, Italy, May 16-18, 2016, Revised selected papers /: 4th International Symposium, ISCO 2016, Vietri sul Mare, Italy, May 16-18, 2016, Revised selected papers. (2016) - Unknown
No abstract available